Synthesis and cytotoxicity of novel 14α-O-(1, 4-disubstituted-1, 2, 3-triazolyl) ester derivatives of andrographolide. Issue 2 (17th January 2021) - Mokenapelli, Sudhakar; Gutam, Madhu; Vadiyaala, Naveen; Yerrabelli, Jayaprakash Rao; Banerjee, Somesh; Roy, Partha; Kancha, Rama Krishna; Kunduru, Bharathi Reddy; Sagurthi, Someswar Rao; Chitneni, Prasad Rao
Abstract: A series of novel 14α- O -(1, 4-disubstituted-1, 2, 3-triazolyl) ester derivatives of andrographolide (5a -n ) were synthesized from andrographolide (1 ). For this endeavour, selective esterification at C-14 hydroxyl group of andrographolide (1 ) with propiolic acid via protection, deprotection strategy followed by 1, 4-regioselective [1, 3]dipolar cycloaddition of alkyne, azide using Cu(I) catalyzed Click chemistry. All the synthesized derivatives were screened for their cytotoxicity on HCT-15, HeLa and K562 cell lines. Compounds 5c and 5j showed highest activity against HCT-15 and K562 cell lines whereas compound 5a displayed activity in all the three cell lines. Loss of cell viability was not observed with the non-transformed cell line MRC-5 with compounds 5j, 5k, 5h and 2 indicating cytotoxic activity of these compounds towards cancer cell lines. Further, molecular docking analysis and SAR studies of highly active compounds 5c and 5j revealed enhanced binding affinity to the target NF-κB protein. Graphical Abstract: